A seara das práticas pedagógicas inclusivas com tecnologias: com a palavra as professoras das salas de recursos multifuncionais - Martins, Claudete da Silva Lima (2012)
In a world of constant and profound transformations, technologies emerge in the school context, creating new possible horizons for the developing of pedagogical practices able to promote the inclusion of students with special educational needs. Searching for knowing and understanding such practices, this study aims to investigate the technologies present in multifunctional resource classrooms in municipal schools in Bagé, RS, as well as the way such technologies are used in inclusive pedagogical practices performed by teachers. The investigation consists of a qualitative research, approaching the characterizing parameters of the multiple case study. The subjects were seven female teachers who work with Special Education, recognized by their pairs for developing good inclusive pedagogic practices. In order to do so, it was used questionnaires, empiric field observation, field diary, interviews, focal group and discursive textual analysis. The theoretical assumptions that beacon this study are based on Freire (2011), Lévy (2006), Moran (2000, 2007), Porto (2009, 2012), Mantoan (2001),Sassaki (2002), Galvão Filho (2009) and Sartoretto and Bersch (2011), without any harm from other collaborations. The study results have showed that the multifunctional resource classrooms from the investigated schools have Assistive Technology resources as well as information and communication technologies which enable teachers to alter, create and recreate their practices. These technologies are used by the teachers in conformity with the needs of the students and their work proposal in the inclusive pedagogic practices they use so that it becomes possible for the student with special educational needs to have access to knowledge and learning, and that the student is able to participate in school activities, able to communicate and socialize. The local teaching system is investing for inclusive policies to become real making it possible for the teachers to participate in continued formation about technologies and be able to have time for discussion time for problems solving as well as cooperative work. These situations, together with a curious open hopeful restless generous cooperative dialogic and loving attitude from the teachers, allow them to perform inclusive pedagogic practices with technologies, inciting the school as a whole to engage in the fight in favor of inclusion.